A previdência rural universalista e a sua relevância na economia dos municípios do Rio Grande do Norte - Carvalho, Juan Pablo Couto de (2010)
This study deals with the rural social security Universalist established by the Constitution of 1988 and its importance in the economy of the municipalities of Rio Grande do Norte. In this context, the study seeks to satisfy two important criteria that guide the selection of objects of social science research: a consideration of issues that have relevance to the real world and the intention to make the contribution to the scholarly literature on theoretical and empirical aspects. The research seeks to reveal what is the economic importance of the subsystem of social security for rural municipalities in RN. The hypothesis is that the transfer of income received by beneficiaries from the rural social security tax exceeds the explicit mechanisms for most municipalities in RN, in many cases significantly, proving the importance of this policy as a mechanism for combating poverty and reducing social inequality, especially before the fragility of the federal system on the national political entity hall. The study presents theoretical cores - chapters 1-3 - and empirical - Chapter 4. The first core is about the evolution of social protection as a state policy, addressing the influential theories and typologies of the State of Social Welfare and the characteristics of the Brazilian social security model, but mainly, its rural social security subsystem, its history until universalistic model inaugurated by the Federal Constitution of 1988. The second begins with an overview of studies that have emphasized the impact of Social Security on the local economy of small municipalities, then passing data and statistics in order to gauge the socioeconomic importance of pension income in the rural municipalities of Rio Grande do Norte. To this end, the final chapter provides a comparison of the monetary value transferred by the payment of social security benefits - rural and urban - to each of the 167 municipalities in RN with the equally important sources of income in the budget of municipal entities. Apart from their own tax revenues, are objects of comparison with the value of pension benefits awarded in RN, transfer quota state relating to the municipality on the federal ICMS and the transfer on the FPM